2010
DOI: 10.1080/00926230903375719
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Erectile Dysfunction as Defined by the International Index of Erectile Function (IIEF) and Self-Reported Erectile Dysfunction in a Sample of Brazilian Men Who Consider Themselves Healthy

Abstract: A cross-sectional study was carried out with 288 male blood donors, aged between 40 and 60 years old, with the aim of comparing the prevalence of erectile dysfunction (ED) as defined by the International Index of Erectile Function (IIEF) and that resulting from the simple questioning of the presence of ED. Socio-demographic, clinical, and behavioral factors that are associated with the presence of ED were considered. Erectile dysfunction prevalence in the IIEF was 31.9%, while self-reported ED prevalence was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Previous studies have demonstrated the accuracy of the IIEF-5© in diagnosing ED compared to the self-reported claims of the sufferers. 16,17 The sample size was calculated using a one-mean formula, as the dependent variables (perceived susceptibility and perceived severity) were continuous data. Authors estimated the sample size based on assumed mean sum score and standard deviation of perceived susceptibility of 2.61 and 1.2, respectively, and for perceived susceptibility of 9.71 and 2.8, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the accuracy of the IIEF-5© in diagnosing ED compared to the self-reported claims of the sufferers. 16,17 The sample size was calculated using a one-mean formula, as the dependent variables (perceived susceptibility and perceived severity) were continuous data. Authors estimated the sample size based on assumed mean sum score and standard deviation of perceived susceptibility of 2.61 and 1.2, respectively, and for perceived susceptibility of 9.71 and 2.8, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The results from this analysis have already been published. 10 The men also gave answers to questions about their own perception of aspects of their personal lives and bodies, such as sexual life, length of relationship with their partner, satisfaction, attraction towards their partner, sexually potency, erection and the satisfaction with their own body and penis size.…”
Section: Methodsmentioning
confidence: 99%
“…We recently communicated the results from a cross-sectional study on the prevalence of erectile dysfunction in men who considered themselves healthy (they were not recruited in hospitals or clinics, and they were healthy enough to be blood donors) and who were not seeking diagnoses or self-information on sexual behavior or function. That study 10 revealed an opportunity to investigate whether those men were satisfied with their penis size. The present study is thus a specific analysis on the previous database.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted until the 1990s in general used convenience samples of health service users or people recruited in public spaces, and this approach may lead to prevalence overestimation because of self-selection or recruitment of individuals in worse health situations. 8 Since the 1980s, there has been a reduction in the response rate to prevalence studies and an increase in costs of conducting studies in general. 9 These factors and the increase in the use of internet from the second half of the decade 10 led researchers to conduct studies on the prevalence of PE using the internet for sampling, recruitment and data collection procedures, with the possibility of including large samples and participants residing in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%